8. “MEDICINE 3.0” AND “5P” IN PROACTIVELY PREVENTING OF BREAST CANCER (Vietnam Journal of Community Medicine, 2025)
Introduction: Advanced breast cancer prevention plays a crucial role in early detection, prevention, and effective treatment, reducing mortality rates, improving quality of life, and extending healthy lifespan for women. According to Globocan 2022, the incidence of breast cancer in Vietnam is remarkably high, with a noticeable trend toward younger cases and a significant mortality rate (8.3%). This article synthesizes medical literature related to proactive health management to help women adopt advanced breast cancer prevention strategies.Results: Medicine 3.0 is a relatively new concept that describes a medical approach focused on prevention and health promotion, rather than merely early detection and timely treatment. The "5P" in Medicine 3.0 include Prediction, Prevention, Personalization, Participation, and Precision, offering an integrated, community-based solution for advanced breast cancer prevention. This approach encourages women to take proactive, individualized, and precise measures for breast cancer prevention.Conclusion: It is essential to promote the application of Medicine 3.0 and the "5P" framework to enhance the effectiveness of breast cancer prevention, reduce mortality rates, and extend the healthy lifespan of Vietnamese women.
Keywords: prediction; prevention; breast cancer; Medicine 3.0; 5P; healthspan